1998
DOI: 10.1093/humrep/13.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Fertility results after ovarian transposition for pelvic malignancies treated by external irradiation or brachytherapy

Abstract: The aim of this study was to assess the fertility outcome after ovarian transposition with uterine conservation and pelvic irradiation therapy for pelvic cancer. A total of 37 consecutive cases were reviewed. Of these, 27 patients were treated for a clear cell adenocarcinoma of the vagina and/or the cervix (group 1), nine for an ovarian pure dysgerminoma and one for a para-uterine soft tissue sarcoma (group 2). The pregnancy rate was 15% (4/27) in group 1 and 80% (8/10) in group 2 (P=0.01). A total of 18 pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 14 publications
0
58
0
Order By: Relevance
“…Spontaneous pregnancies have been reported in women with transposed ovaries, without the need for re-positioning of ovaries (34). However, if infertility develops and in vitro fertilization is needed after ovarian transposition, oocyte retrieval may be more complicated (35).…”
Section: Potential Benefit Of Ovarian Transposition (Oophoropexy)mentioning
confidence: 99%
“…Spontaneous pregnancies have been reported in women with transposed ovaries, without the need for re-positioning of ovaries (34). However, if infertility develops and in vitro fertilization is needed after ovarian transposition, oocyte retrieval may be more complicated (35).…”
Section: Potential Benefit Of Ovarian Transposition (Oophoropexy)mentioning
confidence: 99%
“…A systematic review and meta-analysis of the outcomes of ovarian transposition in gynaecological cancers found that it was associated with the preservation of ovarian function [37] and successful pregnancy outcomes have also been reported [38], however metastases in transposed ovaries and recurrence have been reported [39]. Although this technique would not be suitable for all and care must be taken with case selection since non-squamous histology, stage and unaffected peripheral stromal thickness have been shown to be significantly associated with an increased risk of recurrence [40], it may prevent the onset of menopause in a proportion of cases as well as opening up the possibility for oocyte retrieval and pregnancy through surrogacy [41].…”
Section: Ovarian Transpositionmentioning
confidence: 99%
“…Patients must be informed about the risks of surgical laparoscopy, although surgical laparoscopy is associated with a low rate of complications. Serious complications such as organ injury or secondary bleeding requiring treatment occur in fewer than 1 % of all laparoscopies [27,28]. However, transposition of the ovaries does not protect against the gonadotoxic side effects of chemotherapeutic drugs.…”
Section: Transposition Of the Ovariesmentioning
confidence: 99%
“…GnRH analogs are administered up to 2 weeks before the start of chemotherapy as well as during chemotherapy. In addition to ovarian suppression, GnRH analogs administered to patients with hormone receptor-positive breast cancer also have an inhibitory effect on tumor cell growth [28]. Patients with hormone receptor-expressing breast cancer should therefore be informed about the benefits of treatment with GnRH analogs and their limited side effects.…”
Section: Cryopreservation Of Ovarian Tissuementioning
confidence: 99%